Perancangan Sistem Informasi Penjualan Produk Desain Interior Berbasis Web pada Creative Interior Design - Richard Andrean; I Nyoman Purnama; Putri Anugrah Cahya Dewi (Jurnal Teknologi Terpadu, 2026)
The rapid advancement of technology and widespread internet usage has driven digital transformation across various sectors, including interior design businesses. Creative Interior Design, established in 2003, faces challenges in product marketing, inventory management, and reaching a broader audience, despite utilizing social media platforms. However, these platforms have limitations in presenting detailed portfolios and maintaining consistent promotional reach. This study proposes the design of a web-based sales information system using the prototype method, allowing iterative development based on user feedback. The system integrates portfolio displays, service descriptions, and e-commerce features to support the direct sale of custom furniture products. The goal is to enhance operational efficiency, customer trust, and the company’s competitiveness in the digital market. This initiative is expected to serve as a strategic solution for interior design SMEs in improving customer satisfaction and achieving sustainable business growth.